تحسين استخدام عرض الحزمة في الشبكة عن طريق إعادة توزيع الآلة الافتراضية Virtual Machine - حنا, جبر; اسماعيل, سام (Latakia University Journal -Engineering Sciences Series, 2019)
researchers in networks and communications. These factors are the delay in time, bandwidth, and other factors, which improve the efficiency of the network and provide a better service level, especially with the spread of real-time applications that require taking into account the time limits during the provision of services because overriding restrictions may lose network interest. The bandwidth is a key parameter in the operation of any network, and the communication media in the network plays the largest role in determining the bandwidth, depending on the type of communication medium, whether wired or wireless, and the extent of its resistance to interference. Therefore, hardware improving of bandwidth requires a lot of time And effort, which prompted researchers to go to the software methods to improve this parameter. The aim of this paper is to improve the bandwidth of the network by redistributing the virtual machines on physical machines so that we reduce the overload on network interfaces and distribute this load more appropriately to the rest of the network connections. MATLAB was used to build a software application interface to perform the required operations in this research. MATLAB was chosen as it provides a large number of tools and software components that enrich engineering fields, including communications, networks, systems and information. تُعد عوامل جودة الخدمة من أهم المجالات التي تستقطب اهتمام الباحثين في الشبكات والاتصالات، وتتمثل هذه العوامل في التأخير الزمني وعرض الحزمة والمردود وغيرها من العوامل التي يؤدي تحسينها إلى زيادة كفاءة عمل الشبكة وتقديمها لمستوى خدمي أفضل خاصة مع انتشار تطبيقات الزمن الحقيقي والتي تتطلب التقيد بحدود زمنية معينة أثناء تقديم الخدمات لأن تجاوز القيود قد يُفقد الشبكة الفائدة المرجوة منها. يشكل عرض الحزمة بارامتراً أساسياً في عمل أي شبكة وتلعب وسائط الاتصال في الشبكة الدور الأكبر في تحديد عرض الحزمة إذ يعتمد في طبيعته على نوع وسط الاتصال سواءً كان سلكياً أو لاسلكياً ومدى مقاومته للتشويش، لذلك فإن تحسين عرض الحزمة مادياً هو أمر مكلف ويتطلب الكثير من الوقت والجهد، وهذا ما دفع الباحثين إلى التوجه للطرق البرمجية لتحسين هذا البارامتر. يهدف هذا البحث إلى تحسين بارامتر عرض الحزمة في الشبكة عن طريق إعادة توزيع الآلة الافتراضية Virtual Machine على الأجهزة المضيفة Physical Machine بحيث نخفض من الحمل الزائد على الوصلات الشبكية وتوزيع هذا الحمل بالشكل الأنسب على باقي وصلات الشبكة. تم في البحث استخدام الماتلاب لبناء واجهة تطبيق برمجي من أجل القيام بالعمليات المطلوبة في هذا البحث، حيث تم اختيار الماتلاب نظراً لكونه يقدم عدد كبير من الأدوات والتوابع البرمجية التي تغني المجالات الهندسية بما فيها مجال الاتصالات والشبكات ونظم والمعلومات.